Perubahan Karakter Belajar Mahasiswa Di Tengah Pandemik Covid-19: Tinjauan Sosio-Psiko terhadap Perubahan Karakter Belajar Mahasiswa di tengah Pandemik COVID-19, di Kota Sorong, Papua Barat - Leuwol, Natasya; Gaspersz, Sherly (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2020)
The purpose of this research are to identify and obtain information about, changes in student learning characteristics in the midst of COVID-19 pandemic, using online distance learning systems. The research uses action research procedures in the form of cycles consisting of four stages, namely planning, action, observation and reflection, while the method used is analytical descriptive method, describing the phenomenon of change occur factually, then analyze the phenomenon of change. Respondents for this study were lecturers and students at four universities in Sorong City, with data collection duration of less than 1 month. The results of this research are, there are changes in the character of learning, experienced by students when doing distance learning online, namely mastery of technology is still lacking, the addition of internet quota fees. There is a change in the character of learning experienced by students namely, Intensional changes, positive-active changes, and effective-functional changes. Keywords: Changes in learning character, Students, COVID-19 Pandemic.